PERANCANGAN GAME VISUAL NOVEL “SONDER” UNTUK MENINGKATKAN KESADARAN REMAJA TERHADAP KESEHATAN MENTAL SESAMA - Verrel, Felicia Joscelind; Rahmadianto, Sultan Arif; Sukmaraga, Ayyub Anshari (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
Mental health issues are one of the topics that are often discussed, debated, and even become a trend in recent years, but are still considered trivial and difficult to see, the results of a survey for data collection aimed at young people between the ages of 15 to 25 also show that sufferers of mental health problems are quite common and many of them are not or little aware that people around them also have a high possibility of suffering from mental health problems. This design does not aim to cure mental health problems completely, but rather to cultivate the seeds of empathy and emotional intelligence for young people to increase awareness of mental health, starting from themselves. Game version 1.0 has been tested on seven testers and received positive responses from the psychological side and the design side. This design uses qualitative research methods with survey data collection techniques, observations, interviews, and literature studies accompanied by design thinking methods. This design is also supported by supporting media in the form of merchandise such as acrylic stands, lanyards, fans, hats, tumblrs, tote bags, button pins, sketchbooks, cellphone cases, mouse pads, stickers, shoes, key chains, t-shirts, hats, and mugs. For future researchers who plan to develop video games or similar designs, it is hoped that they will improve the accuracy of the representation of mental disorders, develop research methods, and explore other video game platforms.